Soil microorganism biodiversity in pule (Alostonia scholarus L.) and candlenut trees (Aleurites moluccana L.) at Wijaya Kusuma Campus Surabaya - Isrianto, Pramita Laksitarahmi; Marmi, Marmi; Joeniarti, Elika (Edubiotik : Jurnal Pendidikan, Biologi dan Terapan, 2024)
A beautiful and fresh environment is visible with lush trees that illustrate the level of soil fertility and the diversity of microbes in it. Plant growth and development are influenced by the abundance of soil microbes, which reflect soil fertility and soil biological properties. Wijaya Kusuma Campus Surabaya is a campus whose slogan is Keluruhuran Jiwa Berbenah Lingkungan (Keji Beling) as a form of concern for the environment and the desire to create a healthy environment, it is necessary to explore the existence of potential microbes from the roots of trees in the campus environment. The purpose of this study was to determine the number and type of soil microbial isolates isolated from the rhizosphere of pule (Alostonia scholarus L.) and candlenut (Aleurites moluccana L.) trees on the Wijaya Kusuma Campus Surabaya. This research is exploratory descriptive qualitative research. Research methods include microbial isolation in the rhizosphere of pule and candlenut plants, macroscopic and microscopic characterization of microbes, KOH test, and catalase test. Data were analyzed descriptively describing the number and type of isolates. The results of the study concluded that the isolation results from the Pule tree obtained 12 colonies of fungi and the Candlenut tree obtained 6 colonies. The genus found were Aspergillus flavus, Aspergillus niger, Fusarium sp., Penicillium sp. In addition, 27 bacterial colonies were found on the pule tree and 23 bacterial colonies on the candlenut tree, namely the genus Bacillus sp. The isolate results obtained can be used as microbial observation material in biology learning.